Reactivation of Epstein Barr virus by a dual-responsive fluorescent EBNA1-targeting agent with Zn2+-chelating function. - Jiang,L; Lung,HL; Huang,T; Lan,R; Zha,S; Chan,LS; Thor,W; Tsoi,T; Chau,H; Boreström,C; Cobb,S; Tsao,SW; et al. (Proceedings of the National Academy of Sciences of USA, 2019)
Epstein-Barr nuclear antigen 1 (EBNA1) plays a vital role in the maintenance of the viral genome, and is the only viral protein expressed in nearly all forms of EBV latency and EBV-associated diseases including numerous cancer types. To our knowledge, no specific agent against Epstein Barr virus (EBV) genes or proteins has been established to target EBV lytic reactivation. Here we report an EBNA1- and Zn2+- responsive probe (ZRL5P4), which alone could reactivate EBV lytic cycle through specific disruption of EBNA1. We have utilized the Zn2+ chelator to further interfere with the higher order of EBNA1 self-association. The new bioprobe ZRL5P4 can respond independently to its interactions with Zn2+ and EBNA1 with different fluorescence changes. It can selectively enter the nuclei of EBV-positive cells and disrupt the oligomerization and oriP-enhanced transactivation of EBNA1. ZRL5P4 can also specifically enhance Dicer1 and PML expression, molecular events which had been reported to occur after the depletion of EBNA1 expression. Importantly, we found that the treatment with ZRL5P4-alone could reactivate the EBV lytic induction by expressing the early and late EBV lytic genes/proteins. The lytic induction is likely mediated by disruption of EBNA1 oligomerization and the subsequent change of Dicer1 expression. Our new probe ZRL5P4 represents the first EBV protein-specific agent to potently reactivate EBV from latency, leading to the shrinkage of EBV-positive tumours, and our study also suggests the association of EBNA1 oligomerization with the maintenance of EBV latency.